Pengaruh Model Pembelajaran Kooperatif Tipe Teams Games Tournament (TGT) terhadap kemampuan lari estafet pada siswa kelas VIII SMP Santa Theresia - Paysha Kaniadinanty; Fauzi Miftakh; Irfan Zinat Achmad; Ruslan Abdul Gani (Jurnal Porkes, 2026)
Athletics education, especially in relay running at Santa Theresia Junior High School, faces problems of low student interest and technical mastery. This condition is caused by monotonous teaching methods that lack interaction and cooperation among students. Therefore, this study aims to examine the effectiveness of the Teams Games Tournament (TGT) cooperative learning model in improving the relay running skills of eighth-grade students. This study used a quantitative approach with a one-group pretest-posttest design. The sample consisted of 46 students selected through total sampling. Data were collected through relay running skill tests in the pretest and posttest phases, then analyzed using a paired sample t-test with the help of SPSS version 27 software. The results of the analysis showed a significant increase in the average score, from 47.61 to 81.74, with a significance value of 0.000 (< 0.05). These findings indicate that the application of the TGT model effectively improves mastery of basic techniques, speed, and coordination in relay running. Based on these results, it can be concluded that the TGT type of cooperative learning model has a positive and significant effect on students' relay running abilities, while also increasing active involvement, teamwork, and learning motivation in the Physical Education, Sports, and Health learning process.